Tuberculous mastitis presenting as a lump: a mimicking disease in a pregnant woman case report and review of literature. Issue 5 (October 2014) - Brouwer, A.; Degrieck, N.; Rasschaert, M.; Lockefeer, F.; Huizing, M.; Tjalma, W.
<x content-type="archive" xml:space="preserve">Abstract</x> Tuberculosis (TB) of the breast is a rare entity, and can be confused with many other breast disorders, like mamma carcinoma or inflammatory breast cancer. When finding granulomatous mastitis (GM) on histology, it is important to make a differential diagnosis and seek actively for clues on the presence of tuberculosis, sarcoidosis, Wegener's granulomatosis, or idiopathic granulomatous mastitis, since treatment strategies differ and maltreatment has major implications on morbidity and mortality. An extensive clinical evaluation, laboratory work up, and imaging will lead in most cases to the right diagnosis. Anti-tuberculous therapy is the core treatment for breast TB, and surgery is indicated for extensive or persistent residual disease. Here we present a case of tuberculous mastitis and a review of literature on GM.